PENGARUH MEDIA KAPONE (KANCING POSITIF NEGATIF) TERHADAP KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BILANGAN BULAT - Susilawati, Susi; Irawati, Riana; Maulana, M. (Jurnal Pena Ilmiah, 2017)
This research is based on the researcher's interest in the matter of integers. The integrity of the matter of integers, making the students difficult to learn. The purpose of this research is to proving that learning using kapone media is better than conventional. Population in this research is the elementary school at Kecamatan Sumedang Selatan using KTSP curriculum with of class IV in school as many as 30 students. Meanwhile, the sample is the IV grade students of SDN Cikondang I as experimental class and SDN Gunasari as control class. Instruments used such of test mathematical understanding and problem solving abilities. observation sheet student activities and performance teacher, and student journals. Research result with significance level of Î±=0,05 indicates that learning by using kapone media is better than conventional learning in improving students' understanding and problem solving capability.